Demonstrating Tractor Rollover Stability Using Lego Mindstorms and Smartphones - Koc, A. Bulent; Liu, Bo (Journal of Agricultural Systems, Technology, and Management, 2013)
Lego RCX Mindstorms kits have been used for teaching traction and ballasting of tractors in the Agricultural Equipment and Machinery course at the University of Missouri for several years. Students design and program autonomous model tractors and observe their performance in a competition involving a simulated tractor pulling a set of weights. With this activity, students observe the effects of drive mechanisms and ballasting on the amount of weight a tractor can pull. In addition to tractor performance activities, we developed a methodology to demonstrate the instabilities taking place during tractor operation on uneven terrain. We used the sensors of a smartphone to monitor the tractor stability on sloping ground. A smartphone application transmitted the data from its inbuilt sensors to a computer over a Wi-Fi network. The physical dimensions of the tractor and the data from the smartphone were used in a mathematical model to determine a stability index value for the tractor operation. The laboratory experiments indicated that the inbuilt sensors of smartphones can be used to wirelessly collect information regarding a tractor’s stability. The developed methodology is suitable for teaching rollover prevention of tractors.